ANALISIS AKAD RAHN PADA PENGGADAIAN SYARIAH - Astina Ria Sophiana; Aulia Syahfitri; Intan Khairani; Lisa Novira (Al-Sharf: Jurnal Ekonomi Islam, 2020)
Pawn is an additional form of agreement in the form of collateral from a principal agreement, namely debt and collateral. Guarantees aim to gain credibility from the creditor. The Islamic pawnshop applies the main contract rahn and imposes a specified administrative fee as the loan amount. The collateral remains the property of the person who pawned, but was controlled by the recipient of the pawn. In sharia pawning techniques, operations can be carried out by a sharia financial institution, namely sharia pawnshop, both as a private institution and a government. As such, the status is an additional contract. This research was conducted to analyze the synchronization of these practices based on sharia principles. The research method used is empirical legal research using a fact approach. The results of this study show that the application of the rahn contract as the main contract contradicts the DSN MUI fatwa and compilation of sharia economic law. Keywords : Pawn